Stand-Level Variation Drives Canopy Water Storage by Non-vascular Epiphytes Across a Temperate-Boreal Ecotone - Hembre, Kate; Meyer, Abigail; Route, Tana; Glauser, Abby; Stanton, Daniel E. (Frontiers in Forests and Global Change, 2021)
Epiphytes, including bryophytes and lichens, can significantly change the water interception and storage capacities of forest canopies. However, despite some understanding of this role, empirical evaluations of canopy and bole community water storage capacity by epiphytes are still quite limited. Epiphyte communities are shaped by both microclimate and host plant identity, and so the canopy and bole community storage capacity might also be expected to vary across similar spatial scales. We estimated canopy and bole community cover and biomass of bryophytes and lichens from ground-based surveys across a temperate-boreal ecotone in continental North America (Minnesota). Multiple forest types were studied at each site, to separate stand level and latitudinal effects. Biomass was converted into potential canopy and bole community storage on the basis of water-holding capacity measurements of dominant taxa. Bole biomass and potential water storage was a much larger contributor than outer canopy. Biomass and water storage capacity varied greatly, ranging from 9 to >900kg ha-1 and 0.003 to 0.38 mm respectively. These values are lower than most reported results for temperate forests, which have emphasized coastal and old-growth forests. Variation was greatest within sites and appeared to reflect the strong effects of host tree identity on epiphyte communities, with conifer-dominated plots hosting more lichen-dominated epiphyte communities with lower potential water storage capacity. These results point to the challenges of estimating and incorporating epiphyte contributions to canopy hydrology from stand metrics. Further work is also needed to improve estimates of canopy epiphytes, including crustose lichens.